Housing Assignment with Restrictions: Theory and Evidence from Stanford University's Campus - Landvoigt, Tim; Piazzesi, Monika; Schneider, Martin (American Economic Review, 2014)
This paper studies housing markets where a subset of houses in a restricted area is available exclusively to a subset of “eligible” buyers. An empirical part shows that houses on Stanford campus (available only to faculty) trade at substantial discounts to comparable houses off campus. The theoretical part describes an assignment model with heterogeneous houses and buyers which predicts such discounts if the matchup of quality and buyer pools is sufficiently different inside versus outside the restricted area. The restriction can distort allocations by making eligible buyers choose either higher or lower qualities than ineligible buyers with the same characteristics.